STUDI KOMPARASI KEEFEKTIFAN MODEL PBL DAN PjBL TERHADAP PENINGKATAN MOTIVASI BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA - Vinda Restianni Devi; Sumarno; Agus Sutono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to describe: 1) Describe students' learning motivation in learning with the PBL and PjBL models, 2) Describe students' critical thinking abilities in learning with the PBL and PjBL models, 3) Analyze the differences in learning motivation and students' critical thinking abilities in learning with PBL and PjBL models. The population in this study was class V students at SDN Tumbrep 01, SDN Tumbrep 02 and SDN Toso 02 in 2022/2023, totaling 67 students, with a total sample from the population. Data collection techniques use test, questionnaire and documentation techniques. . The analysis used includes quantitative and qualitative data analysis. Analysis to test the hypothesis used the ANOVA test, where previously the data was tested for normality, homogeneity and linearity. Qualitative data analysis includes data collection, data reduction, data presentation and data verification. The results obtained from qualitative analysis show that there is a significant difference between the PBL model and the PjBL model on students' critical thinking abilities and learning motivation. This can be seen from the average value of critical thinking skills and learning motivation of experimental class students who study with Problem Based Learning which is greater than the average value of the class which studies with the Project Based Learning model. This proves that the Problem Based Learning model has a positive influence on students' critical thinking abilities and learning motivation.The conclusions of this research are (1) there is a difference in the influence of the PBL and PJBL models on the critical thinking abilities of class V students at SDN Tumbrep 01, SDN Tumbrep 02 and SDN Toso 02, (2) there is a difference in the influence of the PBL and PJBL models on the learning motivation of class V students SDN Tumbrep 01, SDN Tumbrep 02 and SDN Toso 02, (3) the PBL model has a greater influence than the PjBL model on the critical thinking skills and learning motivation of fifth grade students at SDN Tumbrep 01, SDN Tumbrep 02 and SDN Toso 02.